Building maintenance and preservation : a guide for design and management / edited by Edward D. Mills. - Mills, Edward D. (Edward David) (Butterworth-Heinemann, 1994)
If modern buildings are designed well then subsequent problems relating to maintenance can be reduced, saving money and greatly avoiding inconvenience to users. The contributors to this book show how to implement this general idea.